(untitled) (Research, Society and Development, 2023)
According to the scope review protocol presented in this article, credit is defined as the combination of trust and time, but it also brings risks of default. Companies that offer credit add value to customers, and studies show that private credit has a positive impact on economic growth. However, there are problems of information asymmetry, adverse selection, and moral hazard in the lender-borrower relationship. The objective of this scope review will be to map credit decision support systems for non-financial companies that use negative registry, credit scoring, qualitative analysis with artificial intelligence, and automatic contract generation, precisely to determine if there are solutions of intelligent and adaptable software systems that solve or minimize the problems identified here. The review protocol was developed following the items of the PRISMA Extension for Scoping Reviews (PRISMA-ScR): Checklist and Explanation, and the protocol registration was carried out on the Open Science Framework, which contributes to reliable and reproducible scientific practice. The research will be conducted on relevant databases, with defined eligibility criteria, and the selected studies will be analyzed, and the data will be synthesized in a table to provide a comprehensive overview of existing credit decision support systems.